NEGATIVE CAPITAL IMPACT ON INVESTMENT AND ECONOMIC GROWTH - Hussein Zaboon Oleiwi (Scholars Digest Publishing, 2024)
The purpose of this research is to measure the impact of capital on investment and economic growth in Iraq, thus contributing to the economic development that Iraq seeks to achieve. The study concluded that there is a waste of human resources as human resources and capabilities are not optimally exploited. This can be explained by the following: First, low spending on education compared to developing countries that have achieved high growth rates, in addition to the lack of optimal use of these expenses, and second, insufficient educational results. The incompatibility of higher education with the needs and requirements of the labor market, which ultimately leads to weak capital investment in economic development, which negatively affects economic growth. Finally, capital is separated from the labor component while integrating the skills, competencies and training necessary for the country's economic growth process
Keywords: negative impact, economic growth, investment, capital.